Improvements in the methodology to study the bottom fishing footprint in the NRA using VMS and logbook data - Sacau-Cuadrado, María del Mar; Durán-Muñoz, Pablo; Garrido, Irene; Baldó, Francisco (2020)
To understand the extent of fishing activities within NAFO Regulatory Area (NRA), a characterization of distribution of fishing effort for a four-year period (2016 to 2019) was carried out. This characterization was done on the basis of two data sources: Haul by haul logbook information and Vessel Monitoring System (VMS) data. The results indicate that logbook data and VMS are complementary and the coupling of both datasets is a powerful methodology for describing the spatial distribution of fishing activity. The objective of this document is to describe some problems detected on the original “coupling VMS with Logbook data” methodology (NAFO, 2017) and suggest the improvements developed in order to tackle them by the implementation of a new “coupling VMS with Logbook data” methodology. Problems detected in the quality of VMS and Logbook data are also raised by this study. NO